2017
DOI: 10.1038/s41598-017-13075-y
|View full text |Cite
|
Sign up to set email alerts
|

Anodal tDCS applied during multitasking training leads to transferable performance gains

Abstract: Cognitive training can lead to performance improvements that are specific to the tasks trained. Recent research has suggested that transcranial direct current stimulation (tDCS) applied during training of a simple response-selection paradigm can broaden performance benefits to an untrained task. Here we assessed the impact of combined tDCS and training on multitasking, stimulus-response mapping specificity, response-inhibition, and spatial attention performance in a cohort of healthy adults. Participants train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 39 publications
4
38
0
Order By: Relevance
“…the probability of any given stimulus, given the context of task A ceases to serve as a reasonable model for the probability of a given stimulus, given the context of task B. Multitasking costs remained higher when the covariance between stimulus representations was high (hi), relative to low (lo). The predicted reductions in MT costs look similar to previous observations, for example B) where participants completed a multitasking paradigm over multiple training sessions (taken from (Filmer, Lyons, et al 2017) . Additionally, the observed increase in costs for high relative to low covariances in stimulus representations looks analogous to previous observations that even over thousands of trials, participants take longer to respond to stimuli that potentially share higher covariances (panel C, Irrelevant stimuli) relative to those with lower covariances (Relevant stimuli).…”
Section: Matching Stimulus Inputs To Task Templatessupporting
confidence: 84%
“…the probability of any given stimulus, given the context of task A ceases to serve as a reasonable model for the probability of a given stimulus, given the context of task B. Multitasking costs remained higher when the covariance between stimulus representations was high (hi), relative to low (lo). The predicted reductions in MT costs look similar to previous observations, for example B) where participants completed a multitasking paradigm over multiple training sessions (taken from (Filmer, Lyons, et al 2017) . Additionally, the observed increase in costs for high relative to low covariances in stimulus representations looks analogous to previous observations that even over thousands of trials, participants take longer to respond to stimuli that potentially share higher covariances (panel C, Irrelevant stimuli) relative to those with lower covariances (Relevant stimuli).…”
Section: Matching Stimulus Inputs To Task Templatessupporting
confidence: 84%
“…However, others have suggested that tDCS, with or without WMT, needs repeated administration to induce long-term potentiation (Alonzo, Brassil, Taylor, Martin, & Loo, 2012;Meinzer et al, 2014), yet others have suggested that tDCS has little effect on cognitive function at all (Horvath, Forte, & Carter, 2015). Within the literature, the strength and duration of current delivery is also varied, but generally kept within 1 milliampere (mA) administered for approximately 5 to 30 minutes with few studies providing stimulation on the upper end of this duration (Clarke, Browning, Hammond, Notebaert, & MacLeod, 2014;Filmer, Lyons, Mattingley, & Dux, 2017;Nitsche et al, 2003;Ruf et al, 2017). If a brief but concentrated tDCS-WMT training paradigm can produce changes in core cognitive capabilities, such an intervention can be easily transported and utilized in a variety of contexts where WM is impacted.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, studies that have combined training and tDCS seem to find little benefit over training alone, which is in contrast to work in younger adults (e.g. Filmer et al, , 2017bLooi et al, 2016;. Nevertheless, the small number of studies here with considerable variability in protocols suggests a potential area for future research.…”
Section: Discussionmentioning
confidence: 67%
“…Critically, repeated sessions of tDCS have been shown to induce long-term potentiation (LTP) and long-term depression (LTD)-like changes in underlying brain regions in young and older adults, suggesting that stimulation could lead to more substantial alterations in neuroplasticity (Di Lazzaro et al, 2012;. It is largely due to this property that tDCS has received attention as a potential treatment for age-related cognitive decline and multi-tasking paradigms (Filmer, Lyons, Mattingley, & Dux, 2017b) following four days of combined training and tDCS, which persisted at a two-week follow-up. Furthermore, Looi et al (2016) found working memory benefits after two sessions of mathematics training combined with tDCS, which were sustained two months following the intervention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation